Case Study and Design Flare Package System for Waste Gas - A D Astuti, Yuliusman (International Journal of Advanced Science and Technology, 2020)
This study examines the important issue to determine flare header size extension from original location to new location of acid flare to prevent damage caused by overpressure. Gas flaring is a common practice used in many industrial processes such as refinery, petrochemical, and oil-gas industry to release flue gas. It is a must-have safety requirement which is installed to reduce excess pressure when the plant is shut down for annual repair, start up or emergency circumstance. With case study and design flare packages system will get additional information because acid flare system has been designed based on the largest single risk with consideration of acid content. Methods flare design studies will be using thermo-hydraulic model. The modelling will be simulated using AspenTechs FLARENET software with some scenario from existing acid flare system design basis for non-simultaneous relieving load and then new acid flare will receive additional load from new unit. From the result of simulation, without changing the size of tailpipe will cause the failure of PSV when the fire case occurred. So, start up without changing size of pipes is not recommended, change some tailpipe 3” into 4” to ensure sufficient back pressure during fire case, for CV failure scenario to ensure back pressure sufficient during CV fail scenario, change type PSV from balance to pilot type